Effects of expanded whole soybeans on growth performance and nutrient digestibility in nursery pigs - Cao, H.; Hines, Robert H.; Jiang, J.M.; Park, J.S.; Froetschner, J.R.; Maloney, C.A.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
As expected, ADG, ADFI, F/G, and digestibility of DM and N were improved in nursery pigs when cone pressure was increased during dry and moist expanding of whole soybeans. These response were quadratic for the most part, such that 1,000 psi was optimal with dry expanding and 700 to 800 psi was optimal with moist expanding.
Keywords: Swine; Expander; Soybeans; Nursery pigs